2016
DOI: 10.3109/13668250.2016.1253051
|View full text |Cite
|
Sign up to set email alerts
|

Conundrums of supported living: The experiences of people with intellectual disability

Abstract: Background Dissatisfaction with the inflexibility of the group home model has led to the growth of supported living that separates housing from support and is thought to have greater potential for better quality of life outcomes. Comparative studies have had mixed findings with some showing few differences, other than greater choice in supported living. By investigating service user experiences of supported living this study aimed to identify how the potential of supported living might be better realised. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 25 publications
2
42
0
8
Order By: Relevance
“…Freedom and exerting personal control across multiple life domains was strong among people in supported living among 34 people with intellectual disabilities in an Australian qualitative study (Bigby et al, ). Like Bigby et al () the IRN findings indicated some participants struggled to assert autonomy when support staff or family restricted choices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Freedom and exerting personal control across multiple life domains was strong among people in supported living among 34 people with intellectual disabilities in an Australian qualitative study (Bigby et al, ). Like Bigby et al () the IRN findings indicated some participants struggled to assert autonomy when support staff or family restricted choices.…”
Section: Discussionmentioning
confidence: 99%
“…Freedom and exerting personal control across multiple life domains was strong among people in supported living among 34 people with intellectual disabilities in an Australian qualitative study (Bigby et al, ). Like Bigby et al () the IRN findings indicated some participants struggled to assert autonomy when support staff or family restricted choices. In their comparison of people with intellectual disabilities living alone versus those in residential care, Bond and Hurst () found a clear preference for living alone given the greater experience of freedom, space and privacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As many of these people were no longer their clients, it was uncertain how many letters actually reached the addressee. Many of the supported living participants were recruited from the earlier qualitative stage of the study, which had used a similar method of recruitment (as reported in Bigby, Bould, & Beadle-Brown, 2016). The criteria for inclusion were people aged 18 years or over, self-identification as a person with intellectual disability, in receipt of a disability service funded by the Department of Human Services, and a supported living arrangement (i.e., living alone, or with no more than two other people who were not parents or siblings, where housing and support were separated).…”
Section: Recruitment and Description Of Participantsmentioning
confidence: 99%
“…This limited progress is typically understood through the binary of presence and participation and explained as due to weak programme implementation or service design (Beadle-Brown, Bigby, & Bould, 2015;Mansell, Beadle-Brown, Whelton, Beckett, & Hutchinson, 2008). Commonly identified factors include poor staff practices, such as group-based outings and use of anonymous public spaces (Bigby, Clement, Mansell, & Beadle-Brown, 2009;Walker, 1995); inadequate staff training or supervision; misinterpretations of policy intent by staff (Beadle-Brown et al, 2015;Bigby & Wiesel, 2015;; or design problems such as omission of support for building social relationships (Bigby, Bould, & Beadle-Brown, 2016). suggest that lack of conceptual clarity may be an explanatory factor that impedes effective service design and delivery by hindering communication, understanding of goals and agreement among stakeholders.…”
mentioning
confidence: 99%